The Obedience of Hajj: Problems and Its Implementation and Effort to Achieve Their Compatibility - Yahya, Umar (Jurnal Adabiyah, 2022)
This research aims to improve the understanding and implementation of the fifth pillar of Islam for the people of Sidenreng Rappang by balancing the observance of Hajj with the other four pillars of Islam so that there are no differences in its application. The method used in this research is a qualitative method with phenomenological approach. The result found that the Muslim community's understanding of Hajj's obligations is far from the correct teachings caused by the educational background of the Hajj candidates is 46.84% from elementary school graduates. Most of the Hajj information comes from family 50%, and Hajj candidates based on work background Most of them are housewives 63.40%. Dominant factors that influence this research include the low level of legal awareness of the community and adherence to the teachings of Hajj 35%, and the desire of the community to get a Hajj title that can be a source of pride in their lives 76.66%. Therefore, it is necessary to develop an emotional relationship and cooperation between the Hajj organizers, both the government and the private sector, to realize the purpose of the pilgrimage, which is obedience to Allah's Shari'a. الـمُلَخَّصُ تهدف هذه الدراسة إلى تحسين فهم وتنفيذ الركن الخامس من أركان الإسلام لأهل سيدرنرينغ رابانج من خلال موازنة تنفيذ الحج مع أركان الإسلام الأربعة الأخرى بحيث لا يوجد فرق في تطبيقها. الطريقة المستخدمة في هذه الدراسة هي طريقة نوعية ذات منهج ظاهري. ووجدت نتائج الدراسة أن فهم المجتمع الإسلامي لواجب الحج بعيد كل البعد عن التعاليم الصحيحة لأن الخلفية التعليمية للحج المرتقب هي 46.84٪ من خريجي المدارس الابتدائية. تأتي معلومات الحج في الغالب من 50 ٪ من الأسرة ، والحجاج المرتقبون على أساس الخلفية العملية هم في الغالب ربات البيوت 63.40 ٪. ومن العوامل المهيمنة التي أثرت على هذا البحث قلة الوعي بقانون المجتمع والالتزام بتعاليم الحج بنسبة 35٪ ، ورغبة المجتمع في الحصول على لقب الحج الذي يمكن أن يكون فخرًا لحياتهم بنسبة 76.66٪. لذلك ، لا بد من بناء علاقة عاطفية وتعاون بين القائمين على أداء العمرة ، الحكوميين والأفراد ، لتحقيق الغرض من الحج ، وهو طاعة شرع الله. الكلمات المفتاحية: تنفيذ الحج ، الطاعة ، المرشحون للحج ، أركان الإسلام Abstrak Penelitian ini bertujuan untuk meningkatkan pemahaman dan pelaksanaan rukun Islam yang kelima bagi masyarakat Sidenreng Rappang dengan menyeimbangkan pelaksanaan haji dengan empat rukun Islam lainnya sehingga tidak ada perbedaan penerapannya. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan fenomenologis. Hasil penelitian menemukan bahwa pemahaman masyarakat muslim tentang kewajiban haji jauh dari ajaran yang benar disebabkan latar belakang pendidikan calon haji adalah 46,84% dari lulusan sekolah dasar. Informasi haji sebagian besar berasal dari keluarga 50%, dan calon haji berdasarkan latar belakang pekerjaan Sebagian besar ibu rumah tangga 63,40%. Faktor dominan yang mempengaruhi penelitian ini antara lain rendahnya kesadaran hukum masyarakat dan ketaatan terhadap ajaran haji 35%, dan keinginan masyarakat untuk mendapatkan gelar haji yang dapat menjadi kebanggaan dalam hidupnya 76,66%. Oleh karena itu, perlu dibangun hubungan emosional dan kerjasama antara penyelenggara haji, baik pemerintah maupun swasta, untuk mewujudkan tujuan ibadah haji, yaitu ketaatan pada syariat Allah. Kata Kunci: Pelaksanaan Haji; Ketaatan; Calon Haji; Rukun Islam